Road to actualized democracy : a psychological exploration - Wagoner, Brady, 1980-; Brescó de Luna, Ignacio; Glaveanu, Vlad Petre (Niels Bohr professorship lectures in cultural psychology., 2018)
"Democracy is the worst form of government, except for all the others" once remarked Winston Churchill. In this day and age this quotation resonates more than ever. This book explores democracy from the perspective of social and cultural psychology, highlighting the importance of the everyday basis of democratic practices. This approach takes us beyond the simple understanding of democracy in its institutional guise of free elections and public accountability, and towards a focus on group dynamics and personal characteristics of the democratic citizen, including their mentalities, habits and ways of relating to others. The book features discussions of the two-way street between democracy and dictatorship; conflicts within protests, ideology and public debate; and the psychological profile of a democratic citizen and its critique. While acknowledging the limitations of today's democratic systems, this volume aims to re-invigorate democracy by bringing psychology to the table of current debates on social change and citizenship"--